2019
DOI: 10.1021/acs.energyfuels.9b03754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrothermal Carbonization Conditions on the Combustion and Kinetics of Wheat Straw Hydrochar Pellets and Efficiency Improvement Analyses

Abstract: Hydrothermal carbonization conditions can affect the combustion and kinetics of wheat straw hydrochar pellets. Temperature and time are the key influencing factors of the hydrothermal carbonization reaction. Hence, exploring the effects of hydrothermal carbonization temperature and time on the combustion and kinetics is of great significance, which can also summarize the conditions for efficiency improvement. Herein, the chemical characteristics and surface microstructures of hydrochar and the combustion chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The peaks at 2920 cm − 1 , 2850 cm − 1, and 1470 cm − 1 are C-H stretching vibration which was contributed by CS llers and LLDPE [19]. The peaks at around 1735 cm − 1 and 1600 cm − 1 were caused by C = O stretching vibration, C = C stretching vibration, and C-O stretching vibration contributed to the peaks at 1160 cm − 1 , 1100 cm − 1 and 1040 cm − 1 [20]. These functional groups were contributed by the main components (cellulose, hemicellulose, lignin) of CS.…”
Section: Ftirmentioning
confidence: 94%
“…The peaks at 2920 cm − 1 , 2850 cm − 1, and 1470 cm − 1 are C-H stretching vibration which was contributed by CS llers and LLDPE [19]. The peaks at around 1735 cm − 1 and 1600 cm − 1 were caused by C = O stretching vibration, C = C stretching vibration, and C-O stretching vibration contributed to the peaks at 1160 cm − 1 , 1100 cm − 1 and 1040 cm − 1 [20]. These functional groups were contributed by the main components (cellulose, hemicellulose, lignin) of CS.…”
Section: Ftirmentioning
confidence: 94%
“…The presence of KOH during activation boosted the formation of spherical and porous carbon particles that enhanced the adsorptive potential of hydrochars. 33 The TEM micrographs of hydrochar samples portrayed the formation of spherical carbon nanoparticles ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a similar reduction in S for the HTC of wheat straw pellets and food waste was observed in previous studies. 51,52 Zhang et al 51 suggested that S was positively correlated with hemicellulose and negatively correlated with the lignin content in biomass. We would like to note that the effect of process type on combustion reactivity varies according to the type of biomass.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, 51 there is a correlation between the char combustion reactivity and fuel ratio (FR) as follows: S decreases with an increase of FR. However, in this study, the results showed no linear relationship between S and FR.…”
Section: Resultsmentioning
confidence: 99%